2014
DOI: 10.1159/000365575
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of MRI-Negative Temporal Lobe Epilepsy Based on PET: A Retrospective Cohort Study

Abstract: Introduction: Using retrospective and comparative methods, we aim to discuss the surgical treatment of magnetic resonance imaging (MRI)-negative temporal lobe epilepsy (TLE) presented with positive positron emission tomography (PET) results. Methods: From the viewpoint of semiology, demography, surgical treatment and prognosis evaluation, we compared 19 MRI-negative, PET-positive TLE patients to 41 TLE with hippocampal sclerosis patients, and then statistically analyzed the differences between these 2 cohorts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…In a retrospective review of 60 cases in China with unilateral TLE, one-third of all patients were cryptogenic groups with positive PET findings. There was no significant difference between surgical outcomes of lesion group and non-lesion group (Engel class I 68.3 and 68.4%, respectively) [22]. Similar study was carried out by LoPinto-Khoury et al with 46 PET-positive cryptogenic TLE cases and 147 mesial temporal sclerosis cases.…”
Section: Neuro-imagingsupporting
confidence: 76%
“…In a retrospective review of 60 cases in China with unilateral TLE, one-third of all patients were cryptogenic groups with positive PET findings. There was no significant difference between surgical outcomes of lesion group and non-lesion group (Engel class I 68.3 and 68.4%, respectively) [22]. Similar study was carried out by LoPinto-Khoury et al with 46 PET-positive cryptogenic TLE cases and 147 mesial temporal sclerosis cases.…”
Section: Neuro-imagingsupporting
confidence: 76%
“…It exhibits high sensitivity in detecting the epileptogenic zone (EZ) of cortical dysplasia (CD), which is known to occur in refractory epilepsy patients. Hence, FDG-PET contributes to localizing seizure onset zone (SOZ) in epilepsy surgery (6,7). It has furthermore demonstrated high sensitivity to detect hyper-metabolic areas in patients with refractory epilepsy (8).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of PET has been reported in several previous studies. For example, reports have shown that good surgical outcome is best predicted by the presence of hypometabolism in PET images, while the presence or absence of MRI pathology adds no further value to the predictive value of PET ( Carne et al, 2004 ; Choi et al, 2003 ; Feng et al, 2014 ; Gok et al, 2013 ; Kuba et al, 2011 ; LoPinto-Khoury et al, 2012 ; Struck et al, 2011 ; Yang et al, 2014 ). When comparing the predictive value of PET, MRI, and DTI, Thivard et al (2011) found that PET carries the most useful information to identify the SOZ, while DTI added predictive value only for cases with PET-negative findings.…”
Section: Discussionmentioning
confidence: 99%